Rapid Implementation of a Novel Embedded Senior Medical Student Program, as a Response to the Educational Challenges of COVID-19 - May, Jennifer; Grotowski, Miriam; Walker, Tim; Kelly, Brian (International Journal of Practice-based Learning in Health and Social Care, 2021)
As with many OECD countries, graduating medical students have been choosing specialist careers at a greater rate than ever before. Generalism in the form of family (general practice) and more generalist medical specialties have been trending down resulting in distributional geographic challenges. With the advent of COVID-19 in March 2020, medical schools and in particular the Joint Medical Program situated in a regional and rural area in NSW Australia had the unique opportunity to rethink the penultimate year curriculum when the previous rapid rotation model through numerous medical specialities became untenable. The need to vision a new practical pragmatic curriculum spurred a rapid revaluation of assessment, placement length and model with a pivot to an “embedded senior student placement” agnostic of discipline and supported by a competency-based learning portfolio. This article explores the barriers and enablers and identifies the potential elements of this type of placement which can be adapted to community and smaller rural sites. The positive student and supervisor experience also enabled an employment model to be woven into the students learning and ensured on hand medical student workforce for hospitals throughout the rural footprint. The capacity of these placements to celebrate variation in experience and support students to learn on the job have now caused a revision of the penultimate year with expectation of gains in students’ satisfaction and in employability. It has also opened up options to deliver and increase the inherent value of generalist placements with likely long term workforce benefit.